Injectable methods for lifting the corners of the mouth (Journal of Face Aesthetics, 2024)
Introduction. The appearance of the face changes with age. The skin loses its firmness, and the levels of collagen and hyaluronic acid decrease. Skin tissues begin to succumb to the effects of gravity, leading to the drooping of the corners of the mouth.Aim. The aim of this study is to discuss injectable methods for the treatment of drooping mouth corners based on selected literature.Material and methods. Scientific databases, including PubMed and Google Scholar, were analyzed. Articles were selected based on inclusion and exclusion criteria.Results. Injectable treatment methods using botulinum toxin, hyaluronic acid, or a combination of both substances are possible.Conclusions. The simultaneous application of botulinum toxin and hyaluronic acid appears to be beneficial.
Keywords: aesthetic medicine; drooping mouth corners; botulinum toxin; collagen; platelet‑rich fibrin